Systemic absorption of propranolol hydrochloride from buccoadhesive films - Pandit J.K. (My University, 2025)
The systemic absorption of propranolol hydrochloride (PHL) delivered through rabbit oral mucosa was studied. Drug-loaded buccoadhesive films of varying compositions with unidirectional drug release were applied to rabbit oral mucosa and inhibition of isoprenaline-induced tachycardia was achieved. In vitro drug release followed zero-order kinetics. The ex vivo mucoadhesivity tests using rabbit small intestinal mucosa on an in-house fabricated apparatus yielded correlation between film composition and mucoadhesivity. Selected batches of placebo films showing good bioadhesion and oral mucosal compatibility in human volunteers could form a basis of propronalol delivery through this route to avoid first pass metabolism.